Participatory research and planning in practice. - (:unkn) unknown (Springer Open, 2020)
The book provides in-depth insights into participatory research and planning by presenting practical examples of its use. In particular, it describes theoretical and methodological aspects of participatory research and planning, as well as the implementation of participatory processes in fields such as transport planning, cultural heritage management, environmental planning and post-earthquake recovery. Further, it compares participatory planning experiences from different territorial levels – from the macro-regional, e.g. Southeastern Europe, Mediterranean or European metropolitan regions, to national, regional and local levels.The book will help researchers, planners, public administration officials, decision-makers and the general public to understand the advantages, disadvantages and constraints of participatory planning and research. Using various examples, it will guide readers through the theory of participatory planning and research, its methods, and different perspectives on how to use it in practice.
Keywords: Partizipation; Regionalforschung; Regionalplanung; Planungstheorie; Planungsprozess; Metropolregion; Biosphärenreservat; Denkmalpflege; Wiederaufbau; Erdbebenschaden; Bewohnerbeteiligung; Planungsebene; Planungsraum; Planungspraxis